(untitled) (Al-Farooq Journal of Sciences, 2026)
This study aimed to investigate the effect of blended learning on developing administrative communication skills among female Educational Administration students at the Faculty of Education, Al-Zawiya. A quasi-experimental one-group pretest–posttest design was employed, using a comprehensive census of all 71 seventh- and eighth-semester students، The study used a 24-item Administrative Communication Skills Scale covering four dimensions: verbal, nonverbal, written, and electronic communication, in addition to eight items used to verify the implementation of blended learning، The results showed a high level of blended learning implementation (M = 4.09/5)، The overall mean of administrative communication skills increased from 3.01 at pretest to 3.34 at posttest, with a statistically significant difference (t = 7.053, p < .001) and a large effect size (Cohen’s dz = 0.837)، Significant improvements were found across all four dimensions, with electronic administrative communication showing the largest effect size (0.888)، The study concludes that blended learning is effective in developing administrative communication skills and recommends expanding its use in Educational Administration courses while strengthening practical activities.